A mixed integer linear programming model for multi-satellite scheduling - Chen, Xiaoyu; Reinelt, Gerhard; Dai, Guangming; Spitz, Andreas (European journal of operational research, 2019)
•We propose an exact mixed integer linear program for agile satellites scheduling.•The model includes time window distributions and observation resource capacities.•Conflict indicators of visible time windows constitute central decision variables.•Using 5-index variables obviates the need for a Big-M approach.•We feasibly reach an optimality gap of less than 2.5% on all test instances. We address the multi-satellite scheduling problem with limited observation capacities that arises from the need to observe a set of targets on the Earth’s surface using imaging resources installed on a set of satellites. We define and analyze the conflict indicators of all available visible time windows of missions, as well as the feasible time intervals of resources. The problem is then formulated as a mixed integer linear programming model, in which constraints are derived from a careful analysis of the interdependency between feasible time intervals that are eligible for observations. We apply the proposed model to several different problem instances that reflect real-world situations. The computational results verify that our approach is effective for obtaining optimum solutions or solutions with a very good quality.